The Impact of School Principal Leadership, Academic Supervision, and Achievement Motivation on Teacher Performance - Firman Edi; Sudadio Sudadio; Isti Rusdiyani; Suryadi Suryadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This Research aims to ascertain the relationship between school principal leadership, academic supervision, and achievement motivation on teacher performance. Method: This Research employs a statistical survey methodology to guarantee the precision of the findings. To provide forecasts, researchers used the partial least squares-structural equation model (PLS-SEM) to ascertain the magnitude of latent variables. The research utilized the Smart PLS. The investigation occurred at a public elementary school in Tangerang, Indonesia's Banten province. Two hundred fifty elementary school teachers from Tangerang City, Banten, Indonesia, were selected as the research sample. A random sampling method was employed to conduct the sampling. Results: This research presents four noteworthy and statistically significant findings, building upon earlier research and discussion. An important factor is the direct connection between the principal's leadership and academic supervision, which exhibits a positive association. The principal's leadership has a direct and beneficial impact on teacher performance. There is a positive association between academic supervision and teacher performance. There is a positive association between achievement motivation and teacher performance. Novelty: This research presents novelty research that combines the variables of achievement motivation, academic supervision, principal leadership, and teacher performance into a single research topic. Furthermore, the current research distinguishes itself from prior investigations through its research emphasis, subjects, and participants. This research is novel in its attempt to incorporate multiple variables into a single unit for investigation and exploration. This research is intriguing due to variations in emphasis, research participants, and incorporation of research factors compared to earlier research.